Neuromuscular development in the emerging scyphozoan model system, Cassiopea xamachana: implications for the evolution of cnidarian nervous systems - Amplatz, Klara; Zieger, Elisabeth; Abed-Navandi, Daniel; Weissenbacher, Anton; Wanninger, Andreas (Frontiers in Neuroscience, 2024)
The scyphozoan Cassiopea xamachana is an emerging cnidarian model system for studying regeneration, animal-algae symbiotic relationships, and various aspects of evolutionary biology including the early emergence of animal nervous systems.Cassiopea has a life cycle similar to other scyphozoans, which includes the alternation between a sessile, asexual form (polyp) and a sexually reproducing stage, the medusa.The transition between the two forms is called strobilation, where the polyp releases a miniature medusa, the iconic ephyra, that subsequently develops into the adult medusa. Common scyphozoan life cycle stages include a sessile polyp, free swimming ephyra larva, medusa, and sexually produced planula larvae. In addition, Cassiopea polyps may reproduce asexually by budding off free-swimming so-called planuloid buds. While the development of planuloid buds and polyps has been studied in some detail, little is known about the ontogeny of the sexually produced planula larva. Using immunofluorescence labeling and confocal microscopy, we examined neuromuscular development during metamorphosis of the planula larva into the juvenile polyp in C. xamachana. For this purpose, we used α-tyrosinated-tubulin, FMRFamide and serotonin-like immunoreactivity together with phalloidin labeling. Our results show a planular nervous system that consists of a basiectodermal neural plexus with mostly longitudinal oriented neurites. This neural meshwork is connected to sensory neurons in the superficial stratum of the ectoderm, which are exclusively localized in the aboral half of the larva. During settlement, this aborally concentrated nervous system of the planula is replaced completely by the orally concentrated nervous system of the polyp.Mature Adult polyps show an extensive nerve net with a loose concentration around the oral disc. These findings are consistent with data from other scyphozoans and most likely constitute a conserved feature of scyphozoan discomedusae. Taken together, the data currently available suggest an aborally concentrated nervous system including sensory cells as part of the neural ground pattern of cnidarian planula larvae. The reorganization of the nervous system from anterior to posterior in planula-to-polyp metamorphosis most likely also constitutes an ancestral trait in cnidarian evolution.